Design of Rectangular Microstrip Antenna Using Inset Feed and DGS Methods for Digital Television at 598 MHz Frequency - Hardiwansyah, Muttaqin; Purnamasari, Dian Neipa; Ms, Achmad Ubaidillah; Haryanto, Haryanto; Ulum, Miftachul (Signal and Image Processing Letters, 2025)
The development of a microstrip antenna for digital TV applications at the center frequency of 598 MHz has been carried out to meet the needs for optimal signal reception in urban areas such as Surabaya. In this research, a microstrip antenna is designed, simulated, and fabricated to verify its performance. The simulation results show that the antenna has a return loss of -12.27 dB, VSWR 1.639, bandwidth 359 MHz, gain 2.26 dBi, and an omnidirectional radiation pattern. After the fabrication process, antenna performance measurements show a return loss of -25.78 dB, VSWR 1.849, and bandwidth 154 MHz. Discrepancies between simulation and fabrication results are mainly due to manufacturing tolerances and material variations. Nevertheless, the results obtained show that the developed microstrip antenna has good performance and is suitable for digital TV applications at the targeted frequency, with the ability to receive signals omnidirectionally which is very important in dense urban environments.